2010
DOI: 10.1007/978-3-642-12465-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Extreme-Value Copulas

Abstract: Being the limits of copulas of componentwise maxima in independent random samples, extreme-value copulas can be considered to provide appropriate models for the dependence structure between rare events. Extreme-value copulas not only arise naturally in the domain of extreme-value theory, they can also be a convenient choice to model general positive dependence structures. The aim of this survey is to present the reader with the state-of-the-art in dependence modeling via extreme-value copulas. Both probabilist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
142
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 96 publications
0
142
0
1
Order By: Relevance
“…see, e.g., [8]. It is observed that the empirical value for Spearman's Rho approximates the theoretical value with increasing n, as implied by the theory.…”
Section: De Nition 21 (Cumulative Hazard Processmentioning
confidence: 54%
“…see, e.g., [8]. It is observed that the empirical value for Spearman's Rho approximates the theoretical value with increasing n, as implied by the theory.…”
Section: De Nition 21 (Cumulative Hazard Processmentioning
confidence: 54%
“…in terms of a function : [12,15,19] whose analytical characterization is given in [3,34]. The stable tail dependence function of the Gumbel copula with parameter ρ ∈ (0, 1) is given, for all…”
Section: Gumbel and Galambos Brought Togethermentioning
confidence: 99%
“…In addition the interval [0.75k opt , 1.25k opt ] seemed to be a reasonable choice to account for the error in the selection of the optimal sample fraction. We tried two different choices of copulas to describe the asymptotic dependence structure of the field, namely the Gumbel copula (Gudendorf and Segers (2010)) and the t-copula (Frahm, Junkera, and A. (2003)).…”
Section: Simulationsmentioning
confidence: 99%